Autophagy and Rheumatoid Arthritis: Current Knowledges and Future Perspectives - Vomero, Marta; Barbati, Cristiana; Colasanti, Tania; Perricone, Carlo; Novelli, Lucia; Ceccarelli, Fulvia; Spinelli, Francesca Romana; Di Franco, Manuela; Conti, Fabrizio; Valesini, Guido; Alessandri, Cristiano (Frontiers in Immunology, 2018)
Autophagy is a degradation mechanism by which cells recycle cytoplasmic components to generate energy. By influencing lymphocyte development, survival and proliferation, autophagy regulates the immune responses against self and non-self antigens. Deregulation of autophagic pathway has been recently implicated in the pathogenesis of several autoimmune diseases, including Rheumatoid Arthritis (RA). Autophagy indeed, seems to be involved in the generation of citrullinated peptides, and also in apoptosis resistance in RA. In this review, we summarize the current knowledges on the role of autophagy in RA and we discuss the possibility of a clinical implication of autophagy modulation in this disease.